Organizing Committee: QAI 2025 (2025 IEEE International Conference on Quantum Artificial Intelligence (QAI), 2025)
Background Intersectional forms of stigma and discrimination related to HIV status, sexual orientation, and other factors may undermine engagement in HIV care and viral suppression. This US national study examined whether the effects of intersectional discrimination on viral suppression are indirectly associated through mental health, substance use, stress, and social support in sexual-minoritized men (SMM) with HIV. Setting Data from the American Remote Contact HIV Epidemiology Study followed a national cohort of SMM living with HIV. Methods We cross-sectionally examined the direct associations of intersectional stigma and viral suppression in addition to indirect paths through mental health (eg, depression), substance use (eg, stimulant use), perceived stress, and social support between November 2023 and October 2024. The HIV-related Stigma Engagement in Care and Health Outcomes Framework guided the path analyses. Results Participants (N = 1000) had a mean age of 43 years ( SD = 11), and identified as White (45.0%), Black (39.8%), or Hispanic/Latino (20.9%). Overall, 86% were virally suppressed. In the path model, intersectional discrimination was indirectly linked to lower probability of viral suppression through increased stimulant use (β = 0.25, P < 0.001; indirect effect β = -0.10, P = 0.018) and tobacco use (β = 0.22, P <0.001); indirect effect (β = -0.14, P < 0.001). Conclusions Findings support a model in which intersectional stigma may adversely affect HIV outcomes through its influence on substance use. Addressing intersectional stigma and supporting mental health and substance use treatment may improve viral suppression among SMM living with HIV.